2004
DOI: 10.1097/01.hjh.0000125441.28861.9f
|View full text |Cite
|
Sign up to set email alerts
|

Renal xanthine oxidoreductase activity during development of hypertension in spontaneously hypertensive rats

Abstract: Renal XOR induction in SHRs does not precede the development of hypertension, but progress concomitantly with an increase in SBP. The results indicate a role for locally synthesized XOR in the development of hypertension-associated end-organ damage, but no major role in the development of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…Antihypertensive effect Lack of antihypertensive effect Apocynin Prevented/attenuated mineralocorticoid-induced hypertension [86,240] Prevented/reversed glucocorticoid-induced hypertension [241] Prevented/reversed adrenocorticotropic hormone-induced hypertension [242] Prevented the development of Ang II-induced hypertension in mice [186] Prevented the development of renovascular hypertension [243] Prevented the development of hypertension induced by RAS activation [50] Reduced blood pressure in borderline and spontaneous hypertension [244] Attenuated salt-sensitive hypertension [245] Normalized blood pressure in a model of hypertension induced by disruption of dopamine D2 receptor [246] Failed to prevent the hypertension induced by chronic infusion of endothelin-1 [200] Failed to prevent hypertension in transgenic mice overexpressing renin or angiotensinogen [247,248] Failed to prevent Ang II-induced hypertension in rats [249,250] Gp91ds-tat Attenuated the blood pressure rise induced by Ang II in mice [209] Failed to attenuate salt-sensitive hypertension [251] Allopurinol Attenuated salt-sensitive hypertension [252] Prevented glucocorticoid-induced hypertension [253] Failed to prevent or attenuate mineralocorticoid-induced hypertension [254] Failed to prevent glucocorticoidinduced hypertension [255] Failed to prevent or attenuate adrenocorticotropic-induced hypertension [242] Failed to prevent the development of hypertension induced by the blockade of nitric oxide synthesis [256] Failed to prevent the progression of hypertension in young SHR [257] Oxypurinol Reduced blood pressure in SHR [258] Tempol Attenuated hypertension in SHR [201] Prevented the progression of hypertension in saltloaded SHRSP [259] Attenuated mineralocorticoid-induced hypertension [260] Failed to prevent Ang II-induced hypertension [264] Failed to attenuate hypertension induced by inhi...…”
Section: Drugmentioning
confidence: 99%
“…Antihypertensive effect Lack of antihypertensive effect Apocynin Prevented/attenuated mineralocorticoid-induced hypertension [86,240] Prevented/reversed glucocorticoid-induced hypertension [241] Prevented/reversed adrenocorticotropic hormone-induced hypertension [242] Prevented the development of Ang II-induced hypertension in mice [186] Prevented the development of renovascular hypertension [243] Prevented the development of hypertension induced by RAS activation [50] Reduced blood pressure in borderline and spontaneous hypertension [244] Attenuated salt-sensitive hypertension [245] Normalized blood pressure in a model of hypertension induced by disruption of dopamine D2 receptor [246] Failed to prevent the hypertension induced by chronic infusion of endothelin-1 [200] Failed to prevent hypertension in transgenic mice overexpressing renin or angiotensinogen [247,248] Failed to prevent Ang II-induced hypertension in rats [249,250] Gp91ds-tat Attenuated the blood pressure rise induced by Ang II in mice [209] Failed to attenuate salt-sensitive hypertension [251] Allopurinol Attenuated salt-sensitive hypertension [252] Prevented glucocorticoid-induced hypertension [253] Failed to prevent or attenuate mineralocorticoid-induced hypertension [254] Failed to prevent glucocorticoidinduced hypertension [255] Failed to prevent or attenuate adrenocorticotropic-induced hypertension [242] Failed to prevent the development of hypertension induced by the blockade of nitric oxide synthesis [256] Failed to prevent the progression of hypertension in young SHR [257] Oxypurinol Reduced blood pressure in SHR [258] Tempol Attenuated hypertension in SHR [201] Prevented the progression of hypertension in saltloaded SHRSP [259] Attenuated mineralocorticoid-induced hypertension [260] Failed to prevent Ang II-induced hypertension [264] Failed to attenuate hypertension induced by inhi...…”
Section: Drugmentioning
confidence: 99%
“…21 In addition to effects on the vasculature, xanthine oxidase may have a function in end-organ damage in hypertension. 27 Mitochondria: Mitochondria are a major source and target of ROS. Some of the superoxide produced in the intermembrane space may be carried to the cytoplasm.…”
Section: Vascular Oxidative Stress and Hypertensionmentioning
confidence: 99%
“…[92][93][94][95][96] This situation can be explained by the hyperactivity of xanthine oxidase found in hypertension. 21,27 Exogenous antioxidants Vitamin C. Vitamin C is a potent water-soluble antioxidant. In the vascular wall, it functions as an enzyme modulator that upregulates eNOS and downregulates NADPH oxidase.…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%
“…[1][2][3] One recent experimental study demonstrated that allopurinol, an xanthine oxidase inhibitor, prevented cardiac hypertrophy in rats with negligible effects on blood pressure (BP). 4 In humans, an elevated blood level of UA was reportedly associated with left ventricular hypertrophy (LVH) in hypertensive patients. 5,6 However, the hypertensive state may have confounded or modified the association because it could be related to both LVH and the UA level.…”
mentioning
confidence: 99%